Immune characterization of a Colombian family cluster with SARS-CoV-2 infection (2021)
Introduction: Immunological markers have been described during COVID-19 and persist after recovery. These immune markers are associated with clinical features among SARSCoV- 2 infected individuals. Nevertheless, studies reporting a comprehensive analysis of the immune changes occurring during SARS-CoV-2 infection are still limited. Objective: To evaluate the production of proinflammatory cytokines, the antibody response, and the phenotype and function of NK cells and T cells in a Colombian family cluster with SARS-CoV-2 infection. Materials and methods: Proinflammatory cytokines were evaluated by RT-PCR and ELISA. The frequency, phenotype, and function of NK cells (cocultures with K562 cells) and T-cells (stimulated with spike/RdRp peptides) were assessed by flow cytometry. Anti-SARS-CoV-2 antibodies were determined using indirect immunofluorescence and plaque reduction neutralization assay. Results: During COVID-19, we observed a high proinflammatory-cytokine production and a reduced CD56bright-NK cell and cytotoxic response. Compared with healthy controls, infected individuals had a higher frequency of dysfunctional CD8+ T cells CD38+HLA-DR-. During the acute phase, CD8+ T cells stimulated with viral peptides exhibited a monofunctional response characterized by high IL-10 production. However, during recovery, we observed a bifunctional response characterized by the co-expression of CD107a and granzyme B or perforin. Conclusion: Although the proinflammatory response is a hallmark of SARS-CoV-2 infection, other phenotypic and functional alterations in NK cells and CD8+ T cells could be associated with the outcome of COVID-19. However, additional studies are required to understand these alterations and to guide future immunotherapy strategies.